The Separation of Chloromethane Mixtures and the Recovery of Dichloromethane, Chloroform and Carbon Tetrachloride by Activated Carbon Fibre - Jufang Wu; Lan Ma; Hongyang Zhao; Zijiu Wang (Adsorption Science & Technology)
One type of activated carbon fibre with a high micropore content was used to separate chloromethane mixtures and recover dichloromethane, chloroform and carbon tetrachloride. The adsorption process (which was accompanied by a temperature change of the activated carbon fibre bed) and the desorption process were investigated by the application of fixed-bed techniques. Two interesting and important phenomena were observed: (i) displacement between the adsorbates; and (ii) agreement in time between the breakthrough of the adsorbate and the temperature change of the activated carbon fibre bed. The recovery rate was greater than 96% and the cyclic process took ca. ½ h to complete, both being satisfactory from an industrial viewpoint. The effect of the current blank velocity on the adsorption capacity and obstruction of the activated carbon fibre bed were also investigated in order to provide fundamental data for industrial application.